Optimizing the Gains of PD controller Using Artificial Bee Colony for Controlling the Rigid Gantry Crane System - Yazid, Edwar (INKOM Journal, 2017)
Control position and reduction of swinging of the payload of a rigid gantry crane system is a challenging work because of under-actuated system. This paper addresses challenges by proposing the artificial bee colony (ABC) algorithm to optimize the gains of the PD controller to form what the so-called the artificial bee colony (ABC)-PD controller. The effectiveness of the proposed control algorithm is tested under constant step functions and compared with Ziegler-Nichols (ZN)-PD controller. The results show that the proposed controller produces slower rise time and peak time, but faster settling time than the ZN-PD controller as well as no overshoot under the predefined trajectories.Â  Â